A survey of the oral health needs of the elderly residents of Luwalhati ng Maynila - Martin, Miriam
A survey of the oral health needs of 35 elderly residents of Luwalhati ng Maynila was conducted. Of all the subjects examined, 57.1% were dentulous and 42.9% were completely edentulous. All dentate subjects are in need of prosthetic and surgical treatment, 40% need periodontal treatment and 35% need restorative treatment. Complete dentures account for the majority of prosthetic treatment need among dentate subjects. The major periodontal treatment need is for oral hygiene instructions with scaling and/or root planing or Code 3 of the CPITN method. All completely edentulous subjects need new complete dentures while 46% need surgical removal of epulis fissuratum. Over-all oral health needs is summarized as follows: all subjects need prosthetic treatment, 23% need periodontal treatment, 77% need surgical treatment.